Penggunaan Audio Visual untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam(PAI)XII IPS SMAN 1 Gedung Harapan - Rois Junaedi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This research was conducted with the aim of improving learning outcomes in the subject of Islamic Religious Education (PAI) for class XII IPS students at SMA Negeri 1 Harapan Building in the 2022/2023 academic year through the use of audio- visual learning media in video form. This research is a Classroom Action Research (CAR) which is carried out in three cycles. Each cycle consists of planning, implementing actions, tests, observations and reflections. The research subjects were 25 students of class XII IPS SMA Negeri 1 Gedung Harapan. Sources of data come from teachers and students. The main techniques in data collection using observation and tests, while supporting techniques using observation and documentation. Data analysis using descriptive qualitative analysis techniques. The results showed that the use of Audio Visual media in the form of Video can improve the learning outcomes of Islamic Religious Education (PAI) subjects for class XII IPS students starting from the pre-cycle learning outcomes, cycle I to cycle III. The cognitive domain of pre-cycle 56% increased to 72% in cycle I and again increased in cycle II to reach 84% and increased again in cycle III to reach 92%. In the affective domain, the average percentage increase from cycle I was 56%, increased to 72% in cycle II and increased again in cycle III, 80%. Based on the results of the study, it can be concluded that using video-type audio- visual learning media can improve learning outcomes of Islamic Religious Education (PAI) for class XII IPS students at SMA Negeri 1 Gedung Harapan in the 2022/2023 academic year.